Dysphagia in a Young Man - Jing-Hwa Wey; Jin-Er Lee; Kwang-Hwa Chang; Yen-Nung Lin; Wen-Kuei Chung (Case Reports in Neurology, 2020)
This case report presents oropharyngeal dysphagia due to oromandibular and cervical dystonia, a rare consequence of aseptic meningitis. A 19-year-old male who was diagnosed with aseptic meningitis visited the rehabilitation outpatient clinic for a sense of foreign body in his throat and odynophagia. Repetitive involuntary movements of his facial, tongue, and laryngeal muscles accompanied by lateroanterior torticollis were observed. Videofluoroscopic swallowing study showed inefficient bolus formation due to repetitive rolling of his tongue and vallecular stasis without penetration or aspiration. Dysphagia and odynophagia had brought the patient significant weight loss and frustration. We provided swallowing training to improve the efficiency and safety of swallowing. The patient’s symptoms improved gradually along with body weight gain and emotional stability. Acute-onset oropharyngeal dysphagia is devastating for young adults. A multidisciplinary approach is mandatory for optimal outcome. We share our experience as a team work and emphasize the rehabilitation aspect.